Ms Pengembangan Aplikasi Web “Mentari” (Menulis Terampil Imajinatif) Untuk Keterampilan Menulis Dongeng Siswa Kelas IV: Upaya Meningkatkan Keterampilan Menulis Dongeng Siswa Kelas IV dengan Aplikasi Web "MENTARI" - Wahdah, Faizah; Dadan Djuanda; Prana Dwija Iswara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of digital-based learning media has become one of the innovative alternatives to support an active and engaging learning process. One such form is web-based applications that allow flexible access and integration of various interactive learning contents. This study aims to develop a web application called "MENTARI" as a learning media to improve elementary school students' skills in writing fairy tales. The method used is Design and Development (D&D) with the ADDIE development model. The research subjects involved 35 fourth-grade students and one classroom teacher at SDN Ganeas I, Sumedang. Expert validation from content, media, and language reviewers provided highly positive evaluations regarding the content quality, user interface, and clarity of language used in the application. User trials also showed encouraging responses from both teachers and students in terms of usability and relevance to writing learning objectives. Final evaluation was conducted by analyzing students' written products, which demonstrated improved ability to structure intrinsic elements of a story. These findings suggest that the "MENTARI" web application is appropriate and effective as a learning medium to support elementary students' fairy tale writing skills.